Cytotoxicity of monensin, narasin and salinomycin and their interaction with silybin in HepG2, LMH and L6 cell cultures. Issue 2 (March 2015) - Cybulski, Wojciech; Radko, Lidia; Rzeski, Wojciech
Highlights Assessment of ionophoric polyethers toxicity to hepatoma and myoblast lines; EC50. Protective effects of silybin in course of cytotoxic action of ionophoric polyethers. Silybin increases viability of all the cells impacted by ionophoric polyethers.